A setup for studies of laser-driven proton acceleration at the Lund Laser Centre. (19th December 2014) - Aurand, B.; Hansson, M.; Senje, L.; Svensson, K.; Persson, A.; Neely, D.; Lundh, O.; Wahlström, C.-G.
Abstract: We report on a setup for the investigation of proton acceleration in the regime of target normal sheath acceleration. The main interest here is to focus on stable laser beam parameters as well as a reliable target setup and diagnostics in order to do extensive and systematic studies on the acceleration mechanism. A motorized target alignment system in combination with large target mounts allows for up to 340 shots with high repetition rate without breaking the vacuum. This performance is used to conduct experiments with a split mirror setup exploring the effect of spatial and temporal separation between the pulses on the acceleration mechanism and on the resulting proton beam.